2008
DOI: 10.1681/asn.2007111174
|View full text |Cite
|
Sign up to set email alerts
|

Presence of FoxP3+ Regulatory T Cells Predicts Outcome of Subclinical Rejection of Renal Allografts

Abstract: Subclinical rejection (SCR) of renal allografts refers to histologic patterns of acute rejection despite stable renal function. The clinical approach to SCR is controversial; it would be helpful to identify biomarkers that could determine whether the identified cellular infiltrates were detrimental. For investigation of whether the presence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 30 publications
10
98
2
7
Order By: Relevance
“…In multivariate analysis, higher FoxP3 mRNA levels did not correlate with favorable 6-mo graft outcomes, even when the analysis was restricted to biopsies with rejection. Contrary to this study 22 and in agreement with the results of our study, Bestard et al 23 suggest that immunostaining of FoxP3 ϩ Tregs in protocol biopsies seems to be useful for the prediction of long-term kidney transplant outcome. Similarly, in the mouse renal transplant model, the presence of FoxP3 Tregs decreased during ongoing rejection.…”
Section: Discussionsupporting
confidence: 90%
“…In multivariate analysis, higher FoxP3 mRNA levels did not correlate with favorable 6-mo graft outcomes, even when the analysis was restricted to biopsies with rejection. Contrary to this study 22 and in agreement with the results of our study, Bestard et al 23 suggest that immunostaining of FoxP3 ϩ Tregs in protocol biopsies seems to be useful for the prediction of long-term kidney transplant outcome. Similarly, in the mouse renal transplant model, the presence of FoxP3 Tregs decreased during ongoing rejection.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with previous studies reporting reduced Treg frequencies in solid organ allograft rejection 30 Tregs constitute an attractive therapeutic target given their essential role in controlling autoimmunity. However, recent animal studies provide evidence for functional heterogeneity and lineage plasticity within the Treg compartment.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple studies have demonstrated that Tregs promote postischemic kidney preconditioning and repair, suppress rejection, and induce allograft tolerance in kidney transplantation. [30][31][32][33] Alternately, DCs and macrophages have been shown to worsen ischemic injury through various mechanisms and depletion of these cells protects the kidney from IR injury. [34][35][36][37][38] Although numbers of DCs and macrophages increased after IR compared with baseline kidneys, their number was low in kidneys of CD4-Keap1-KO mice in this study.…”
Section: Discussionmentioning
confidence: 99%